Living through a computer voice: A personal account. (October 2013) - Martin, Alan; Newell, Christopher
Abstract Alan Martin, the first author of this paper, has cerebral palsy and uses a voice output communication aid (VOCA) to speak, and this paper describes the personal experience of living 'through' a computer voice (or VOCA) in the form of an interview of Mr Martin conducted by Dr Newell. The interview focuses on the computerized voice output rather than other features of the VOCA. In presenting a first-hand account of the experience of actually using VOCA, the intention is that both everyday, practical issues of the technology and broader imaginative, philosophical, and sociological implications will be explored. Based upon the interview, the authors offer an informal set of design requirements and recommendations for the development of future VOCAs.